Impact Of Emergency Obstetric Care Skill Training Workshops For Medical Students At Ziauddin University. Karachi. Pakistan - Shazia Sultana; Dr. Shahina Ishtiaq; Dr Rubina Hussain; Natasha Lateef (ziauddin University, 2018)
Background: Obstetric emergencies are usually sudden, unpredictable and may lead to maternal death and morbidity. Each year about 5,36,000 women die worldwide from complications of pregnancy and childbirth. Health professionals should be trained in emergency, life saving skills. Emergency obstetrics skills workshops for medical students were aimed to train them in providing care in emergency situations like antepartum and postpartum haemorrhage, eclampsia, shock, obstructed labour and abortion. Thus the purpose of our study was to evaluate the effect of emergency obstetrics workshop after providing training in team work in fourth year medical students to fulfil our future needs. We have evaluated the effect of hands-on training of emergency obstetrics skills in medical students in small groups and assessed the difference in their knowledge before and after the workshop. Methods: This cross-sectional study was conducted at Obstetrics and Gynaecology Department of Ziauddin University, Karachi, Pakistan from 2015 to 2016. Fourth year MBBS students (n=146) were included in the study with their informed consent. The knowledge regarding pre & post workshop was evaluated regarding various emergency situations with the help of a questionnaire. A pre-workshop test of 10 multiple-choice questions was administered to all the participants. At the end of the workshop, the same 10 questions were administered and the two scores compared using Paired sample t-test for paired data on SPSS statistical software version-21. A paired-sample t-test was for pre & post test score. Results: The results of pre test and post test showed profound improvement. We have been observed that the post test mean value of knowledge was higher than the pretest mean value of knowledge. Finally p-value <0.05 was considered statistically significance. Students were able to identify basic need of obstetric care that should be provided in obstetric emergency, compared with the situation before receiving the training. Conclusion: Well defined and structured hands-on training is an effective way of improving skills of medical students and may reduce maternal mortality in Pakistan.